Palaeolithic archaeology of the Bytham River: human occupation of Britain during the early Middle Pleistocene and its European context. (6th April 2021) - Davis, Rob; Ashton, Nick; Hatch, Marcus; Hoare, Peter G.; Lewis, Simon G.
ABSTRACT: The Early and early Middle Pleistocene archaeological record in Britain from c. 900 to 500 ka marks a critical shift in human occupation of northwest Europe, from occasional pioneer populations with simple core and flake technology to more widespread occupation associated with the appearance of Acheulean technology. Key to understanding this record are the fluvial deposits of the extinct Bytham River in central East Anglia, where a series of Lower Palaeolithic sites lie on a 15 km stretch of the former river. In this paper we present the results of new fieldwork and a reanalysis of historical artefact collections of handaxes and scrapers to: 1) establish the chronostratigraphic context of the Bytham archaeological record; 2) examine variability in lithic artefact typology and technology through time; and 3) explore the implications for understanding variation in lithic technology in the European record. Six phases of occupation of Britain are identified from at least marine isotope stage (MIS) 21 to MIS 13, with the last three phases characterised by distinctive lithic technology. We argue that this relates to the discontinuous occupation of Britain, where each phase represents the arrival of new groups derived from different European populations with distinctive material culture.